Berufliche Infektion mit Trichophyton verrucosum bei einem Rinderzüchter - Schumny, Uta (Hautarzt, 2020)
Ringworm in cattle may cause an occupational skin disease in humans. Trichophyton verrucosum lead to a highly inflammatory fungal skin infection that is often misdiagnosed as bacterial disease and consequently mistreated with antibiotics. To establish the correct diagnosis, it is necessary to collect skin scales; in addition, a skin biopsy can be helpful. Deep dermatophyte infections by Trichophyton verrucosum can be treated effectively with oral terbinafine. In addition, it is necessary to pay careful attention to use suitable hygiene measures in the stables to protect against reinfection.